The Revised M-OF-K Runs Rules Based On Median Run Length - Low, , Chun Kit. (2011)
Statistical Quality Control (SQC) is a branch of Total Quality Management. SQC deals with the collection, analysis and interpretation of data, for use in quality control activities. Two major parts of SQC are Statistical Process Control (SPC) and acceptance sampling. All planned or systematic actions necessary to provide adequate confidence that a product or service will satisfy given requirements for quality are called quality assurance (Shirland, 1993). Quality assurance is usually associated with some form of measurement and inspection activity and it has been an important aspect of production operations throughout history.